2010
DOI: 10.1007/s12015-010-9124-7
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Telomerase Template Antagonist GRN163L on Bone-Marrow-Derived Rat Mesenchymal Stem Cells is Reversible and Associated with Altered Expression of Cyclin d1, cdk4 and cdk6

Abstract: Telomerase activity is essential for the continued growth and survival of malignant cells, therefore inhibition of this activity presents an attractive target for anti-cancer therapy. The telomerase inhibitor GRN163L, was shown to inhibit the growth of cancer cells both in vitro and in vivo. Mesenchymal stem cells (MSCs) also show telomerase activity in maintaining their self-renewal; therefore the effects of telomerase inhibitors on MSCs may be an issue of concern. MSCs are multipotent cells and are important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…Bone marrow derived MSCs were isolated from rats. Consistent with previous observations by us and others [49][50][51], the cells were positive for mesenchymal stem cell markers such as CD90, CD71, and CD29, and negative for hematopoietic cell lineage markers such as CD34 and CD45 shown by RT-PCR (Fig. 5A).…”
Section: Bone Marrow Derived Mscs Grown On Hydrogel Filmssupporting
confidence: 92%
“…Bone marrow derived MSCs were isolated from rats. Consistent with previous observations by us and others [49][50][51], the cells were positive for mesenchymal stem cell markers such as CD90, CD71, and CD29, and negative for hematopoietic cell lineage markers such as CD34 and CD45 shown by RT-PCR (Fig. 5A).…”
Section: Bone Marrow Derived Mscs Grown On Hydrogel Filmssupporting
confidence: 92%
“…3). Consistent with previous observations by us and others [27,28], our results showed that MSCs were positive for the expression of MSC markers (CD90, CD71 and CD29) but negative for hematopoietic stem cell markers (CD45 and CD34) for all passages as expected at the transcript level (Fig. 3a).…”
Section: Characterization Of Mscssupporting
confidence: 93%
“…4c) and viability (Fig. 5) on collagen coated or non-coated patterned CNTs than in early passage (P0) can be explained by the aging of MSCs [27,38,39]. Gruber et al have shown that the mean percent senescence increased significantly with cell passaging [38] and high passage numbers adversely affected the functioning of stem cells [39].…”
Section: Seeding Mscs On the Patterned Cnt Arraysmentioning
confidence: 95%
“…In the previous studies, chitosan containing interpenetration network has been used as an adsorbent for separation of protein from aqueous medium due to its high contents of amino and hydroxyl functional groups. 45,46 The PEG side-chains onto copolymer membranes can be expected to reduce the interaction between blood (plasma protein and cells) and the membrane surface. As expected, PEG side-chains containing membranes showed reduced platelet adhesion compared to pHEMA, and p(HEMA-HPC)-1-2, and p(HEMA-PEG-MA-HPC) formulations.…”
Section: Lwmentioning
confidence: 99%